ATRACTIVENESS OF Gyropsylla spegazziniana (LIZER, 1917) (HOMOPTERA, PSYLLIDAE) TO COLOURFUL TRAPS - CHIARADIA, LUÍS ANTÓNIO (1997)
This research was carried out in Chapecó, western of Santa Catarina, Brazil, to study the atractiveness to Gyropsylla spegazziniana (Lizer, 1917) (Hom., Psyllidae) to colourful traps in three-year-old flex paraguariensis orchard. The design was randomized blocks with six replicates in time. The five treataments consisted of trays painted with Eive different coloras of "Coral" sintetic oil as follows: white (001); yellow-dark (016); yellow-light (01679); green-light (01862); and red (019). Colourful trays filled with water and detergent were installed between trees on a wood support with 1.30 m high. After 24 hours samples were collected and brougth to laboratory of Epagri-CPPP. Psillids were counted under sterioscopic microscope adjusted to forty times magnificent. The red and yellow-dark traps showed more atiactive than others and can used for monitoring of this kind of insect pest.